Montenegro Policy Notes 2017 - World Bank Group (World Bank, Washington, DC, 2017)
Montenegro and the World Bank Group (WBG) have jointly prepared a robust program of cooperation for the next four years. In the past 18 months, the World Bank Group has prepared the Systematic Country Diagnostic (SCD) for Montenegro, a comprehensive analytic report outlining challenges and opportunities that the country is facing on the road to sustained growth and prosperity, and the Country Partnership Framework (CPF), a document that sets out the goals and priorities for World Bank Group program in Montenegro for the next four years. Both the SCD and the CPF were informed by extensive and broad consultations with the government, local communities, private sector, civil society and international development partners active in Montenegro. In particular, the CPF, World Bank Group strategy in Montenegro that came into force in June 2016, has been developed on the basis of the diagnostic and of the government’s own strategic priorities. Bank’s strategy is focused on two priority areas: Enhancing Macroeconomic and Financial Resilience, and Enabling Inclusive Access to Economic Opportunities and Jobs. The following policy notes summarize the key challenges, policy options and ways in which WBG could provide effective support. These are fully consistent with the recommendations of the Systematic Country Diagnostic and goals of the Country Partnership Framework, and aim to present a concise and clear set of proposals for each priority area. The Notes form a consistent document but each one of them can be used as a stand-alone piece for discussion with the relevant sector stakeholders. There are three thematic Notes outlining key priority areas – macro-fiscal and financial resilience, private sector and jobs, and environmental sustainability. Each of these is accompanied by a series of sector notes that provide additional detail.